Clinical and Computed Tomography Characteristics in Patients with Bilateral Chronic Rhinosinusitis Undergoing Functional Endoscopic Sinus Surgery with Middle Turbinate Resection - Van Dien, Nguyen; Dinh Thi, Dao; Tuan Son, Nguyen; Ngoc Ha, Nguyen; Ngoc, Nguyen; Lan, Hoang (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Abstract: Objective: To describe the clinical and computed tomography characteristics of patients with bilateral chronic rhinosinusitis undergoing functional endoscopic sinus surgery with middle turbinate resection. Subjects and Methods: A cross-sectional descriptive study was conducted on 35 patients with bilateral CRS who underwent FESS with middle turbinate resection. Results: The male-to-female ratio was 1.5:1, with a mean age of 45.9 ± 14.6 years. Nasal obstruction and rhinorrhea were the most common symptoms. Most patients had moderate SNOT-22 scores. Endoscopic examination revealed that grade II and grade III nasal polyps were the most frequent findings and were correlated with the severity of clinical symptoms. On computed tomography (CT) imaging, concha bullosa of the middle turbinate was the most common anatomical variation. Most patients had osteomeatal complex involvement, and partial sinus opacification was observed in 42.86% of cases. Conclusion: Overall, the patients presented with typical and significant clinical manifestations. Computed tomography proved to be a valuable tool for diagnosis and surgical planning in chronic rhinosinusitis with middle turbinate abnormalities. Keywords: Chronic rhinosinusitis, SNOT-22, concha bullosa, paradoxical middle turbinate.